PMO-055 Quality of life following laparoscopic banded (silastic ring) sleeve gastrectomy. (28th May 2012) - Pearless, L; Clarke, M; Booth, M
Abstract : Introduction: Placement of a silastic ring around a sleeve gastrectomy (SG) may minimise long-term dilatation and weight regain. This study assessed medium term quality of life outcomes. Methods: A questionnaire was sent to 46 patients that underwent surgery between November 2006 and February 2010. During the procedure the stomach was divided 3 cm proximal to the pylorus. Orogastric bougie diameter was 36 French (November 2006–June 2008) or 32 Fr (thereafter). A 6.5–7 cm diameter silastic ring was placed around the mid-portion of the SG. Results: Responses were received from 29 (63%) patients (25 female, 4 male) with a mean (range) age of 49 (33–65) years and mean pre-op BMI of 37.5 kg/m 2 . Mean (SD) weight loss and % excess weight loss at 3 years was 31.1 (10.8) kg and 90.6 (28.9)% respectively. 66% were satisfied with surgery (median Likert score=9) although 48% reported weight regain. Physical —97% reported food intolerances: meat (59%), solids (35%) and vegetables (17%). 21 (72%) patients reported vomiting: daily (14%), twice weekly (14%), weekly (29%) or less frequently (43%). 66% had reflux, with a median Visick of 2. Exercise capacity increased in 96% of patients. Emotional —28% described depression or anxiety affecting their work or other activities. Social —28% found physical health /emotional problems following surgery interfered with social activities. Compliance —59% had blood tests at least annually, 79% continued multivitamins and 41% required vitamin/mineral supplementation. Conclusion: Placement of a silastic ring around SG as a primary procedure should be avoided due to a high incidence of post-operative reflux, vomiting and food intolerance. Competing interests: None declared.